A Content Analysis of Counseling Outcome Research and Evaluation (CORE) from 2010 to 2017. (2nd January 2018) - Cade, Rochelle; Gibson, Sandy; Swan, Karrie; Nelson, Kristina
ABSTRACT: In this study, authors reviewed articles published in Counseling Outcome Research and Evaluation from 2010 through 2017. Characteristics associated with authors (i.e., gender, setting, and domicile) and article characteristics (i.e., sample age, sample ethnicity, research paradigm, primary statistical analysis) were coded and analyzed. Professional implications and future recommendations are discussed.